Survival Rate and Growth Performances on Pre-Grossing of the African Cyprinidae LabeobarbusBatesii (Boulenger, 1903) According to the Level of Dietary Protein - Achile Peguy Tonfack; Tekounegning Claudine Tiogué; Nsangou Amidou Kpoumie; Ferdinand Ngoula; kameni Patricia Linda Djikengoue; Tameghe Flora Mambe; Salifou Njouokou; Ewoukem Thomas Efole; Joseph Tchoumboue (International Journal of Aquaculture Research and Development, 2020)
In order to contribute to the domestication of Labeobabusbatesii, the survival and growth performances in pre-grossing according to the dietary protein level were studied between January and April 2020. A total of 400 fry (0.8 ± 0.02g), divided into four batches and distributed randomly in 8 happas (50 ind / m2), respectively received in duplicate the food at 25, 30, 35 or 40% crude protein (R25%, R30%, R35% and R40%). The results show that: survival rate and growth performances were significantly influenced (p≤0.05) by the level of dietary protein except for lengths (total, standard and length gain) whose highest values ​​were obtained with the diet at 35% crude protein, the highest significant values ​​of the other growth characteristics were obtained in the batch fed at 25% crude protein while the lowest were recorded on individuals of batches fed at 40% crude protein. Regardless of the level of food protein, the post-larvae presented an allometric minorant growth. So, 25% of dietary protein is therefore recommended for pre-grossing of this species.
Keywords: Labeobarbusbatesii